2019
DOI: 10.1038/s41416-019-0659-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of quantitative proteome data predicts metabolic reprogramming of liver cancer

Abstract: BACKGROUND: Metabolic alterations can serve as targets for diagnosis and cancer therapy. Due to the highly complex regulation of cellular metabolism, definite identification of metabolic pathway alterations remains challenging and requires sophisticated experimentation. METHODS: We applied a comprehensive kinetic model of the central carbon metabolism (CCM) to characterise metabolic reprogramming in murine liver cancer. RESULTS: We show that relative differences of protein abundances of metabolic enzymes obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…With further study, 37 genes closely associated with carcinogensis in T2DM were revealed, and the interactions among them were concentrated on carbohydrate metabolism as well. These findings are consistent with several published studies [ 24 , 25 ], and provide a promising direction for the investigation of the metabolism-related molecules relevant to the development of HCC and progression of T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…With further study, 37 genes closely associated with carcinogensis in T2DM were revealed, and the interactions among them were concentrated on carbohydrate metabolism as well. These findings are consistent with several published studies [ 24 , 25 ], and provide a promising direction for the investigation of the metabolism-related molecules relevant to the development of HCC and progression of T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we developed a novel approach that combines proteomic analysis of liver tissue with kinetic modeling of liver metabolism. In a preceding work [28], we demonstrated that this approach is capable of correctly predicting the metabolic phenotype of liver tumors in a mouse model. In this work, we used proteomics data on protein…”
Section: Discussionmentioning
confidence: 95%
“…In this special issue, several contributions added essential pieces to this puzzle. For instance, Berndt et al 3 capitalise on a unique in silico modelling approach using proteomics data not only to predict metabolic changes in liver cancer, but also to identify metabolic pathways whose inhibition selectively affects cancer cells. In addition, Becker 4 provides an extensive review of the regulation of pH in cancer cells and proposes the concept of a 'transport metabolon', whereby multiple transporters act together to regulate acid/base homoeostasis in cancer cells, a key regulator of cellular metabolism.…”
Section: Mapping Cancer Metabolismmentioning
confidence: 99%